PERSEPSI MAHASISWA AKUNTANSI TERHADAP ETIKA PENGAJAR AKUNTANSI (Komparatif Studi Pada Fakultas Ekonomi dan Bisnis, Universitas Indonesia) - Arvian Triantoro; Muhammad Rizal Muhsin (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2011)
The research aims to determine student’s perception of students of Accounting Education courses and students of Accounting courses towards the ethics of accounting educators in Faculty of Economics and Business Education, Indonesia University of Education. The analysis is based on the answers obtained through questionnaire of the respondent.Population of the research is all student of Accounting Education courses and student of Accounting courses in Faculty of Economics and Business Education, Indonesia University of Education. The research use purposive sampling method. Sample taken are the student of Accounting Education courses and student of Accounting courses from class of 2007. Both were taken from 40 students.The implementation of reference for the indicator of variable in the ethics of accounting educators is an instrument that is developed by Meilisa and Ludigdo (2010). To test the reliability of the data, Pearson correlation product moment is used while to test the normality of the data, Kolmogorov-Smirnov test is used. Data of Independent Sample T-Test is taken to test the variance of homogeneity and to examine the hypothesis. All data is calculated with the assistance of SPSS 16 software.The result of the study indicates that there is no difference of perception among students of Accounting Education courses and students of Accounting courses toward the ethic of accounting educators. This research also shows that students of Accounting Education course and students of Accounting course have a good perception towards the ethics of accounting educators, which means that accounting educators in Faculty of Economy and Business Education have applied a good ethics in performing their job.